2021
DOI: 10.3329/jom.v22i1.51390
|View full text |Cite
|
Sign up to set email alerts
|

Etiological Evaluation of Acute Confusional State in Elderly (≥60 Years) Patients

Abstract: Background: Acute confusional state or delirium is a frequent cause of hospital admission in the elderly. It is characterized by an acute fluctuating impairment of cognitive functions and inattention. Recognition and prompt treatment is crucial to decrease the morbidity and mortality of hospitalized elderly patients. Aim of this study was to evaluate the distribution of common medical conditions related to acute confusional state among elderly hospitalized Patients. Methods: This was a cross sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Rahman et al study had 380 patients (>60 years), 256 (67.36%) were male, and 124 were female (32.63%) [8]. Aslaner et al study had 52.3% women and 48.7% men [9].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Rahman et al study had 380 patients (>60 years), 256 (67.36%) were male, and 124 were female (32.63%) [8]. Aslaner et al study had 52.3% women and 48.7% men [9].…”
Section: Discussionmentioning
confidence: 97%
“…Rahman et al (2016) study showed that causes of delirium were uncontrolled HTN (63.2%), infection (41.6%), uncontrolled DM (36.6%), and CVD (28.4%). CKD (10.5%) [8]. Sumji Setal conducted study showing most common cause CVA (n=161, 25.6%), metabolic (n=157, 24.9%), infections (n=117, 18.5%), seizures (n=83,13.0%), intracranial infections (n= 32, 5%), ICSOL (n =16, 2.6%), poisoning (n=8, 1.3%), SDH (n=9, 1.5%), and unknown (n=17, 2.7%) [11].…”
Section: Etiologymentioning
confidence: 99%
“…In a study most common medical condition contributes to delirium were uncontrolled hypertension (63.2%), then fever and infection (41.6%), uncontrolled DM (36.6%), CVD (28.4%), CKD and electrolytes abnormalities (10.5%), joint diseases and pain (13.7%). 15 Smoking was also a prevalent risk factor found in patients with CNS infection. In the US physicians' health study, Kurth and colleagues found that current smoking was associated with a twofold increase in the risk of ischaemic stroke (RR 2.11, 95% CI, 1.72-2.60).…”
Section: Discussionmentioning
confidence: 99%